The role of reference point in CEO restricted stock and its impact on R&D intensity in high‐technology firms - Lim, Elizabeth N. K. (Strategic Management Journal, 2015)
Prior work based on agency theory and behavioral agency model has focused on how absolute pay values affect firm outcomes. Departing from this traditional approach, we draw from behavioral decision theory to explain how relative pay levels influence firm risk taking. We investigate how CEO restricted stock value relative to reference point influences R & D intensity in high‐technology firms. We propose that negative deviation increases are related to R & D increases and positive deviation increases lead to R & D decreases, while negative deviation has greater effect than positive deviation. We establish theoretical boundary conditions by considering CEO duality and board vigilance as moderators. Drawing from agency theory, we predict the main effects will be enhanced under duality and weakened under high board vigilance. Our hypotheses are largely supported . Copyright © 2014 John Wiley & Sons, Ltd.